Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

What is the sum of – 2x2 – 5x + 3 and
- 4x2 + 4x – 6?


Sagot :

[tex] - 6 {x}^{2} - x - 3[/tex]

[tex]\large\mathfrak{{\pmb{\underline{\red{Step-by-step\:explanation}}{\orange{:}}}}}[/tex]

[tex]( - 2 {x}^{2} - 5x + 3) + ( - 4 {x}^{2} + 4x - 6) \\ \\ = - 2 {x}^{2} - 5x + 3 - 4 {x}^{2} + 4x - 6 \\ \\Combining \: the \: like \: terms, \: we \: have \: \\ \\ = - 2 {x}^{2} - 4 {x}^{2} - 5x + 4x + 3 - 6 \\ \\ = - 6 {x}^{2} - x - 3[/tex]

[tex]\large\mathfrak{{\pmb{\underline{\orange{Mystique35 }}{\orange{♡}}}}}[/tex]

Answer:

-6x^2 - x - 3

Step-by-step explanation:

(-2x^2 -5x +3) + (-4x^2 + 4x -6)

open the brackets .Remember while opening the brackets signs also get multiplied .

=-2x^2 -5x +3 - 4x^2 + 4x -6

=-6x^2 -x -3

(minus * minus) sign=plus sign

(minus * plus) sign=minus sign

(plus * plus) sign=plus sign

(minus + minus) sign=plus

(plus + plus) sign=plus sign